Vakuum v vesolju - Čekada, Miha (Vakuumist, 2001)
In this paper, vacuum environment in the universe is described. All planets in the Solar system including some satellites have an atmosphere, although some of them are in the range of extremelz high vacuum. The solar wind is the extension of the solar atmosphere into the interplanetarz space. The comets get their typical form by interaction with the solar wind. Interstellar gas clouds, better known as nebulae are also described.
Keywords: vesolje; vakuum; atmosfera; Osončje